CAUSES AND CORRECTION OF PUBLISHING MALPRACTICE IN "STUDENT SCIENCE" - L. V. Kanayeva (Moscow Polytechnic University, 2018)
The article discusses the "publication disease" of student science as a deviation phenomenon of the period of education reforming, and as a phenomenon inherited from the current scientific practice. Using case study method, the author analyzes two versions of students' publications that represent the extreme levels of the deviant range in student publications. The article dwells on the causes of similar deviations in the university environment and gives the concrete proposals to remedy the current situation: 1) to improve the ethics of university science, 2) to form students' research competences properly, 3) to dispose the Russian bibliographic database of junk publications and malpractice journals, 4) to create a special electronic RSCI library of student scholarly works, 5) to adapt a unified normative document regulating academic ethics at universities. The author believes that these measures may improve the state of youth science, make it more transparent and effective.